2002
DOI: 10.1046/j.1462-2920.2002.00349.x
|View full text |Cite
|
Sign up to set email alerts
|

High bacterial diversity of a waste gas‐degrading community in an industrial biofilter as shown by a 16S rDNA clone library

Abstract: The bacterial diversity of an industrial biofilter used for waste gas abatement in an animal-rendering plant was investigated. A 16S rDNA clone library was generated and 444 clones were screened using computer-aided amplified ribosomal DNA restriction analysis (ARDRA). Of the screened clones, 60.8% showed unique ARDRA patterns and the remaining 174 clones were clustered into 65 groups. Almost full-length 16S rDNA sequences of 106 clones were determined and 90.5% of the clones were affiliated with the two phyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 59 publications
7
47
1
Order By: Relevance
“…The values of H and J showed that diversity and evenness of distribution of OTUs over the patterns were quite high and coverage of 82.9% demonstrated that a majority of microbial community was covered in this 16S rDNA clone library. The values obtained in the present study were quite high in comparison with estimates reported for sediments from the Lonar Soda Lake (Wani et al, 2006) and Victoria Harbor sediments in Hong Kong (Zhang et al, 2008), and low in comparison with a waste gas-degrading biofilter (Friedrich et al, 2002).…”
Section: Discussioncontrasting
confidence: 55%
“…The values of H and J showed that diversity and evenness of distribution of OTUs over the patterns were quite high and coverage of 82.9% demonstrated that a majority of microbial community was covered in this 16S rDNA clone library. The values obtained in the present study were quite high in comparison with estimates reported for sediments from the Lonar Soda Lake (Wani et al, 2006) and Victoria Harbor sediments in Hong Kong (Zhang et al, 2008), and low in comparison with a waste gas-degrading biofilter (Friedrich et al, 2002).…”
Section: Discussioncontrasting
confidence: 55%
“…Two previous studies done on microbial community structures of pristine versus contaminated areas of the aquifer at the FRC have found that contamination resulted in a decrease in microbial diversity and selected for Betaproteobacteria species related to or belonging to Azoarcus (22) and Alcaligenaceae (57). Furthermore, Betaproteobacteria were found to be abundant in other contaminated environments, including polychlorinated biphenyl-contaminated soil (50), a waste gas biofilter (26,27), metal-and petroleum-contaminated soil (39), heavy metal-amended soil microcosms (45), and metallurgic wastewater (70). Similarly, our results show that Betaproteobacteria SSU rRNA clones, primarily those affiliated with Alcaligenaceae and Burkholderiaceae, are present in contaminated sediment samples from the FRC (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…2) and were 100% and 97.6% similar to FRC isolate 7.5A2, respectively. Only one clone from FB067 belonged to OTU 34; rather, 87.5% of Betaproteobacteria clones from FB067 belonged to OTU 45, whose closest relative was clone BIsii8 (97.8% similarity), which was identified from an industrial waste gas biofilter (26). Its two closest cultured relatives were Burkholderia brasilensis, an N 2 -fixing bacterium (GenBank accession no.…”
Section: Resultsmentioning
confidence: 99%
“…In this :1 trans2............................................................................... :1 cis9................................................................................... :1 cis9................................................................................... (Table 3). In general, clone libraries seem to underestimate the proportion of gram-positive bacteria detected by other direct methods like cultivation (7,42) or FISH (16). Additionally, members of the Acidobacterium group and the uncultured candidate division TM7 were found in the clone libraries, for which the most similar sequences originated from a soil isolate and from a cloned sequence of hot spring samples, respectively.…”
Section: Vol 71 2005 Microbial Diversity Of Beer Bottling Plant Biomentioning
confidence: 92%